Empowering people with disabilities through social media: a review / Nur Azila Azahari and Dr. Nurullizam Jamiat - Azahari, Nur Azila; Jamiat, Nurullizam (Universiti Teknologi MARA, Kedah, 2023)
Social media serves as an important space for engagement in everyday activities like education, business, politics, and social life. The purpose of this article is to document ways people with disabilities utilize social media and to examine some of the limitations and motivational elements of their use of social media platforms. This systematic literature review contains research articles from respected databases from 2019 and 2023. The articles were selected based on the inclusion and exclusion criteria and then examined and synthesized according to the research questions. The findings highlight the significance of using social media to support people with disabilities in their daily life activities in addition to promoting their independence and skill acquisition through social media platforms. We believe that this work may offer light on the subject for other researchers. It is suggested that further research needs to be done on understanding how social media platforms can enhance the performance and life quality of those with disabilities.